Optical Properties and Biochemical Indices of Marine Particles in the Open Mediterranean Sea: The R/V Maria S. Merian Cruise, March 2018 - Chaikalis, Spyros; Parinos, Constantine; Möbius, Jürgen; Gogou, Alexandra; Velaoras, Dimitris; Hainbucher, Dagmar; Sofianos, Sarantis; Tanhua, Toste; Cardin, Vanessa; Proestakis, Emmanouil; Amiridis, Vassilis; Androni, Afrodite; et al. (Frontiers in Earth Science, 2021)
A rich data set on particulate matter optical properties and parameters (beam attenuation coefficient, volume concentration, particle size and PSD slope), accompanied by measurements of biochemical indices (particulate organic carbon, particulate nitrogen and their stable isotopic composition) was obtained from the surface to deep waters across the Mediterranean Sea, in March-April 2018. A decrease of beam attenuation coefficients, total particle volume concentrations, particulate organic carbon and nitrogen concentrations were noted towards the eastern Mediterranean Sea (EMed) in comparison to the western Mediterranean Sea (WMed). LISST-derived optical properties were significantly correlated with water mass characteristics. Overall, the most turbid water mass identified in the Mediterranean Sea was the Surface Atlantic water (AW), and the most transparent was the Transitional Mediterranean Water (TMW) in the Cretan Sea, whereas a general decrease in particulate matter concentration is observed from the WMed towards the EMed. Relatively depleted δ13C-POC values in the particle pool of the open Mediterranean Sea can be attributed to contribution from terrestrial inputs, mainly via atmospheric deposition. Throughout the entire water column, a significant positive correlation between particle beam attenuation coefficient and particulate organic carbon concentration is observed in the open Mediterranean Sea. Such relationship suggests the predominance of organic particles of biogenic origin. POC concentration and particle median diameter D50 are significantly and negatively correlated both in the WMed and the EMed Sea, confirming that small particles are POC-rich. At depth, a prominent decrease of most measured parameters was observed, with the exception of particle median diameter that increased substantially in the EMed towards the deep sea, suggesting potentially enhanced aggregation processes. The low particle size distribution slope ξ observed in the EMed, corresponding to larger particle populations, supports the above notion. Basin-wide Rayleigh-type isotopic fractionation in vertical profiles of δ15N-PN across the Mediterranean Sea, underlines the differences in the trophic characters of the two sub-basins and highlights the role of circulation changes on biogeochemical parameters and the redistribution of particulate matter as a source of nutrients in the water column.